1999
DOI: 10.1038/sj.bjp.0702700
|View full text |Cite
|
Sign up to set email alerts
|

Anisatin modulation of the γ‐aminobutyric acid receptor‐channel in rat dorsal root ganglion neurons

Abstract: 1 Anisatin, a toxic, insecticidally active component of Sikimi plant, is known to act on the GABA system. In order to elucidate the mechanism of anisatin interaction with the GABA system, wholecell and single-channel patch clamp experiments were performed with rat dorsal root ganglion neurons in primary culture. 2 Repeated co-applications of GABA and anisatin suppressed GABA-induced whole-cell currents with an EC 50 of 1.10 mM. No recovery of currents was observed after washout with anisatin-free solution.3 Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 41 publications
3
72
2
1
Order By: Relevance
“…Fipronil is known to block the GABA A receptor in rat DRG neurons with an IC 50 value of 1.6 M (Ikeda et al, 2001). It blocks both the resting receptors and activated receptors to the same extent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fipronil is known to block the GABA A receptor in rat DRG neurons with an IC 50 value of 1.6 M (Ikeda et al, 2001). It blocks both the resting receptors and activated receptors to the same extent.…”
Section: Resultsmentioning
confidence: 99%
“…Both dieldrin and fipronil potently blocked the insect GABA-gated chloride channels at nanomolar concentrations. Compared with our previous studies with rat dorsal root ganglion (DRG) neurons Ikeda et al, 2001), the blocking action of fipronil on cockroach GABA receptors was much more potent than its action on mammalian GABA A receptors. In contrast, the action of dieldrin on insect GABA receptors was similar to its actions on mammalian GABA A receptors, exhibiting a dual action on GABA-induced chloride currents that manifested as an initial enhancement followed by a dramatic inhibition.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Fipronil is known to block GABA receptors thereby causing hyperexcitation of insects and mammals (Ikeda et al, 2001;Zhao et al, 2003). Fipronil has also been found to be a potent blocker of GluCls (Zhao et al, 2004a, b;.…”
Section: Glutamate-activated Chloride Channel: Unique Chemical Targetmentioning
confidence: 99%
“…We previously reported that naturally occurring terpenoids such as picrodendrins and anisatin exhibit insecticidal activity by binding to the antagonist site of the GABA receptor. [2][3][4][5] Several terpene lactones such as picrodendrin O exhibited selective affinity for the insect versus mammalian GABA receptors. We have also isolated insecticidal alkaloid GABA antagonists from the culture of Aspergillus terreus by binding assay-guided screening.…”
mentioning
confidence: 99%